2019
DOI: 10.1656/045.026.0318
|View full text |Cite
|
Sign up to set email alerts
|

Home Range and Habitat Use of West Virginia Canis latrans (Coyote)

Abstract: Canis latrans (Coyote) has undergone a range expansion in the United States over the last century. As a highly opportunistic species, its home range and habitat use changes with ecological context. Coyotes were first reported in West Virginia in 1950 but were not commonly observed until the 1990s, and there is scant information on Coyotes in the region. We used telemetry data from 8 radiocollared Coyotes in West Virginia to estimate home-range size and third-order habitat selection. Home-range areas (95% utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…To our knowledge, our study is the first to combine high‐resolution spatial data with landscape characteristics to assess fine‐scale movements and space use of both resident and transient coyotes throughout the pup‐rearing season. We found that resident coyotes had home range and core area sizes comparable to those reported in contemporary studies (Hickman et al., 2016; Mastro et al., 2019; Ward et al., 2018) and noted a similar trend in regard to daily movements (Grubbs & Krausman, 2009). It was not surprising that we observed comparable movements and space use with previous studies in the southeastern United States, given the relative consistency of body sizes exhibited by coyotes throughout much of the region (Hinton et al., 2019).…”
Section: Discussionsupporting
confidence: 86%
“…To our knowledge, our study is the first to combine high‐resolution spatial data with landscape characteristics to assess fine‐scale movements and space use of both resident and transient coyotes throughout the pup‐rearing season. We found that resident coyotes had home range and core area sizes comparable to those reported in contemporary studies (Hickman et al., 2016; Mastro et al., 2019; Ward et al., 2018) and noted a similar trend in regard to daily movements (Grubbs & Krausman, 2009). It was not surprising that we observed comparable movements and space use with previous studies in the southeastern United States, given the relative consistency of body sizes exhibited by coyotes throughout much of the region (Hinton et al., 2019).…”
Section: Discussionsupporting
confidence: 86%
“…To determine territorial status of collared animals, we used a combination of ≥3 months of space use by coyotes (Hinton et al, 2015) and a rarefaction curve for each animal created by calculating monthly home ranges (Dellinger et al, 2013). Previous studies have found that resident coyotes in the southeastern U.S. maintain home ranges that range from approximately 5 to 45 km 2 (Hinton et al, 2015, Mastro et al 2019. Thus, we classified resident coyotes as animals that showed stable space use for ≥3 months and had home ranges smaller than 45 km 2 .…”
Section: Movement Data Analysismentioning
confidence: 99%
“…In the United States, research on coyotes ( Canis latrans ) has increased significantly over the last several decades because of the species' recent range expansion (Hinton et al, 2019; Hody & Kays, 2018), role as the top canid predator in most regions (Gompper, 2002; Kilgo et al, 2010; Robinson et al, 2014), ability to live in urban areas (Breck et al, 2019; Gehrt et al, 2009; Lombardi et al, 2017), and hybridization with red wolves ( Canis rufus ; Bohling & Waits, 2015; Hinton et al, 2018; Nowak, 2002) and eastern wolves ( Canis lycaon ; Benson et al, 2012; Rutledge et al, 2012; Wilson et al, 2000). In the southeastern United States, average home range sizes reported for resident coyotes are relatively large (range = 5.2–85.0 km 2 ; Chamberlain et al, 2021; Hickman et al, 2016; Hinton et al, 2015; Mastro et al, 2019; Stevenson et al, 2019; Ward et al, 2018) and consist of a diversity of land cover ranging from open anthropogenic (i.e., urban and agriculture) to dense vegetation cover (Hickman et al, 2016; Hinton et al, 2015; Stevenson et al, 2019; Ward et al, 2018). Recent studies of coyotes in the southeastern United States reported that coyotes tend to select early successional vegetation communities and open landcover types (Hinton et al, 2015; Stevenson et al, 2019) and primarily consume mammalian prey and fruit (Cherry et al, 2016; Hinton et al, 2017, 2021; Schrecengost et al, 2008; Ward et al, 2018).…”
Section: Introductionmentioning
confidence: 99%